Reaffirming the Islamic Tarbiyah Halaqah Educational Model in Fostering Religious Character Among Students at Islamic Boarding School - Ramli; Hanafie, Wardah; Jurumiyah, Abdul Hakim; Halik, Abdul; Yusuf, Mursidin (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to explore the reaffirmation of the Islamic Tarbiyah Halaqah educational model in cultivating religious character among students (santri) at Pondok Pesantren Umar bin Abdul Azis, Tomenawa Village, Baraka Subdistrict, Enrekang Regency. Employing a qualitative descriptive approach, the research utilized primary data collected from caretakers and leaders of the pesantren, as well as secondary data from relevant documents. Data were gathered through in-depth interviews, participant observation, and documentation. The data analysis process involved data reduction, presentation, and verification. The findings indicate that the model emphasizes character development through key religious activities such as congregational prayer, tahsinul qirā’ah (Qur’anic recitation enhancement), and taujihāt (spiritual guidance) provided by murabbis (mentors). The reaffirmation of this model has proven effective in nurturing religious character through the integration of religious instruction, daily practice, and social engagement. Contributing factors include the murabbi’s exemplary and affectionate guidance, the structured halaqah system, and a supportive environment provided by families and peers. In contrast, inhibiting factors include parental neglect in their children’s religious education and negative peer influences that may undermine the values taught within the pesantren. Abstrak: Penelitian ini bertujuan untuk mengkaji penegasan kembali model pendidikan Tarbiyah Halaqah Islam dalam menumbuhkan karakter religius pada santri di Pondok Pesantren Umar bin Abdul Azis, Desa Tomenawa, Kecamatan Baraka, Kabupaten Enrekang. Dengan menggunakan pendekatan kualitatif deskriptif, penelitian ini memanfaatkan data primer yang diperoleh dari para pengasuh dan pimpinan pesantren, serta data sekunder dari dokumen-dokumen terkait. Pengumpulan data dilakukan melalui wawancara mendalam, observasi partisipan, dan dokumentasi. Proses analisis data meliputi reduksi data, penyajian, dan verifikasi. Hasil penelitian menunjukkan bahwa model tersebut menekankan pada pengembangan karakter melalui kegiatan-kegiatan keagamaan utama seperti shalat berjamaah, tahsinul qirā’ah (peningkatan bacaan Al-Qur’an), dan taujihāt (bimbingan spiritual) yang diberikan oleh murabbi (mentor). Penegasan kembali model ini terbukti efektif dalam menumbuhkan karakter religius melalui integrasi pelajaran agama, praktik sehari-hari, dan keterlibatan sosial. Faktor pendukungnya antara lain bimbingan murabbi yang penuh keteladanan dan kasih sayang, sistem halaqah yang terstruktur, dan lingkungan yang mendukung dari keluarga dan teman sebaya. Sebaliknya, faktor penghambatnya antara lain pengabaian orang tua dalam pendidikan agama anak-anaknya dan pengaruh negatif teman sebaya yang dapat merusak nilai-nilai yang diajarkan di pesantren.